Overview of Slope Monitoring Technology. (February 2019) - Yang, Panpan; Wang, Nianqin; Jiang, Zhongyan; Yang, Yan; Yan, Heping
Abstract: The geological disaster caused by slope engineering has always been one of the most concerned issues in the society. In recent years, the rapid development of urbanization in China has caused relatively large changes in the geological environment, sometimes leading to landslides and mudslides, which pose a significant threat to human lives and properties. The monitoring technologies of slope deformation have been rapidly developed and played an increasingly important role in ensuring slope stability. This paper briefly introduces the conventional slope deformation monitoring technologies and their shortages. The latest development of slope deformation monitoring technologies is presented in detail, followed by analysis of the features of these technologies. Finally, some research suggestions are proposed for future development of slope deformation monitoring technologies.